Molecular Identification of Endophytic Fungi from Local Rice and Growth Test on Several Types of Culture Media - Syamsia Syamsia; Abubakar Idhan; Amanda Patappari; Noerfitryani Noerfitryani; Rahmi Rahmi; Iradhatullah Rahim (Hasanuddin University, 2019)
Local rice is rice that has been cultivated for generations by the community and commonly cultivated without using chemical inputs. Endophytic fungi are fungi that live in the plant tissue and does not cause disease symptoms in the host plants. This study aimed to molecular identifying isolates of MDTA and MDTB endophytic fungi which have been isolated from the local Pulu Mandoti rice plant tissue and growth test on the four types of culture media those were synthetic PDA, natural PDA, MPA, and MEA. The fungi DNA isolation using DNesay Kit. DNA sequencing analysis using the mega BLAST program showed that the MDTB fungus has similarities to Podoscypha bolleana strain 32034 no accession JQ675334 and Podoscypha bolleana strain 32032 no accession JQ675332, whereas the MDTA fungus has similarities to Coprinopsis cinerea A2S3-5 isolate and Coprinopsis cinerea strain CNRMA / F 07-32. The best culture media and sporulation of endophytic fungi is MPA media. This research is the first study to molecular identifying with endophytic fungi from local rice and viability test on the four types of culture media. The results of this study contribute to the diversity of local rice endophytic fungi in Sulawesi.